Development and Validation of the Humanistic Practice Ability of Nursing Scale - Jinhua Zhang; Xiaoyan Zhou; Hefang Wang; Yanyan Luo; Wei Li (Elsevier, 2021)
Purpose: The purpose of this study was to develop a Humanistic Practice Ability of Nursing (HPAN) scale adapted to China and validate its psychometric properties. Methods: The original HPAN scale was revised through a literature review. Sixteen experts who met the inclusion criteria were consulted 2 rounds by the Delphi method. According to their suggestions and opinions, the structure, content, and semantics of each item of HPAN were modified, and a HPAN scale was preliminarily developed. The HPAN scale was validated through item analysis, exploratory factor analysis, convergent validity, and reliability. The data came from 406 first-class hospital nurses. Results: A 5-dimension, 29-item HPAN scale demonstrated satisfactory fit with significant factor loadings. The split-half reliability coefficient of the scale was .98, the split-half reliability coefficient of each dimension was .86-.99, Cronbach's α coefficient was .96, and the Cronbach's α coefficient of each dimension was .87-.98. The model fit of the scale was good, and the items of the scale showed convergent and discriminant validity. Conclusion: The HPAN scale indicated that the reliability and validity were good. It is easy to imply factors of HPAN. This scale can be used to assess the HPAN.